Randomized clinical trial of liposomal bupivacaine transverse abdominis plane block versus intrathecal analgesia in colorectal surgery. Issue 6 (28th March 2019) - Colibaseanu, D. T.; Osagiede, O.; Merchea, A.; Ball, C. T.; Bojaxhi, E.; Panchamia, J. K.; Jacob, A. K.; Kelley, S. R.; Naessens, J. M.; Larson, D. W.
Abstract : Background: Transverse abdominis plane (TAP) block is considered an effective alternative to neuraxial analgesia for abdominal surgery. However, limited evidence supports its use over traditional analgesic modalities in colorectal surgery. This study compared the analgesic efficacy of liposomal bupivacaine TAP block with intrathecal (IT) opioid administration in a multicentre RCT. Methods: Patients undergoing elective small bowel or colorectal resection were randomized to receive TAP block or a single injection of IT analgesia with hydromorphone. Patients were assessed at 4, 8, 16, 24 and 48 h after surgery. Primary outcomes were mean pain scores and morphine milligram equivalents (MMEs) administered within 48 h after surgery. Secondary outcomes included duration of hospital stay, incidence of postoperative ileus and use of intravenous patient‐controlled analgesia. Results: In total, 209 patients were recruited and 200 completed the trial (TAP 102, IT 98). The TAP group had a 1·6‐point greater mean pain score than the IT group at 4 h after surgery, and this difference lasted for 16 h after operation. The TAP group received more MMEs within the first 24 h after surgery than the IT group (median difference in MMEs 10·0, 95 per cent c.i. 3·0 to 20·5). There were no differences in MME use at 24 and 48 h, or with respect to secondary outcomes. Conclusion: IT opioid administration provided better immediate postoperative pain control than TAP block. Both modalities resulted in low pain scores in patients undergoing elective colorectal surgery and should be considered in multimodal postoperative analgesic plans. Registration number: NCT02356198 (http://www.clinicaltrials.gov ). Abstract : This prospective multicentre RCT compared the analgesic efficacy of liposomal bupivacaine transversus abdominis plane (TAP) block versus intrathecal opioid administration in colorectal surgery. Intrathecal opioid administration provided better immediate postoperative pain control than TAP block, and this effect lasted for 16 h after surgery. Intrathecal better initially